Problem Based Learning with Metakognitive Strategy to Improve Concept Understanding - Hidayah, Noor; Farumananda, Fatimah Primadian; Darma Putra, Ngurah Made; Sugianto, Sugianto (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
Understanding concepts is one of the abilities students must possess to solve problems. PBL can improve understanding of concepts. One strategy that can be used in learning is metacognitive strategies. Metacognitive strategies help students in thinking about solving problems. This study aims to examine the effect of PBL with metacognitive strategies on the concept of understanding. The study used a qualitative method, while the research design with the type of pre-test post-test control group design. Data retrieval uses reasoned multiple choice questions to measure understanding concepts in optical device materials. The results showed that PBL with metacognitive strategies had an effect on improving understanding of physical concepts. The metacognitive strategies used in PBL learning train students for planning, information management, monitoring, improvement and evaluation in solving physical problems. Concept understanding in the control class using PBL increases with low criteria and the experimental class uses PBL with metacognitive strategies increasing with the medium criteria.